1991
DOI: 10.1530/acta.0.1240331
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of spontaneous pulsatile secretion of human chorionic gonadotropin and pregnancy specific β1 glycoprotein by superfused placental explants in first and last trimester. Lack of episodic human placental lactogen secretion

Abstract: We have recently reported that during superfusion of placental explants, human chorionic gonadotropin secretion is episodic. In the present work we have examined, using the superfusion model, the pattern of secretion of other glycoprotein hormones, pregnancy specific \ g=b\ 1glycoprotein and human placental lactogen, in the first trimester and term placenta. This was done by evaluating the pulsatile pattern by two different computerized programmes. By using different sampling intervals (6-0.5 min) of the efflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…75 Using perfused placental explants as a model, it was found that PSG secretion is pulsatile and the pulse frequency increases with the gesta tional age. 76 Pregnancy-specific β 1 -glycoprotein se cretion rapidly decreases after a term delivery with a half-life value of 29.7 hours and is followed by a second half-life of 72.2 hours. However, the half-lives of PSG after a first-trimester abortion (21.3 and 45.5 hr) are considerably shorter.…”
Section: Psg Synthesis and Expressionmentioning
confidence: 99%
“…75 Using perfused placental explants as a model, it was found that PSG secretion is pulsatile and the pulse frequency increases with the gesta tional age. 76 Pregnancy-specific β 1 -glycoprotein se cretion rapidly decreases after a term delivery with a half-life value of 29.7 hours and is followed by a second half-life of 72.2 hours. However, the half-lives of PSG after a first-trimester abortion (21.3 and 45.5 hr) are considerably shorter.…”
Section: Psg Synthesis and Expressionmentioning
confidence: 99%